Early-Onset Neonatal Sepsis in Low-Birth-Weight and Birth-Asphyxia Infants at Haji Hospital Surabaya, Indonesia (Indian Journal of Public Health Research & Development, 2020)
Introduction: The incidence of early-onset neonatal sepsis is still high, therefore special attention is needed early detection of risk factors for early management. Many risk factors could affect early-onset neonatal sepsis such as birth-weight and birth-asphyxia. Aim: This study explored the risk factors for early-onset neonatal sepsis among neonates at Haji Hospital, Surabaya City, Indonesia. Method: This study was observational analytic with a cross-sectional design. The data used retrospective document review was conducted in NICUs of Haji Hospital, Surabaya City, Indonesia. 1.461 infants were born from January 2018 to December 2018. The data analysis of this study was the Chi-Square Test and Multiple Logistic Regression Test using SPSS for windows v.17. Result: This study involved 1.461 infants with one hundred seventy-eight suffered of sepsis. The study found out that low-birth-weight and birth-asphyxia were significantly associated with neonatal sepsis (p
Keywords: Neonatal sepsis; low?birth?weight; birth?asphyxia.